تكامل المقارنة المرجعية وقياس كلفة النوعية الرديئة لدعم عمل أدارة الجودة - الموسوي, بتول عطية; سلمان, سعدون محسن (Journal of Economics and Administrative Sciences, 2008)
The two quality management concepts of benchmarking and poor quality cost measurement have been developed completely separate from each other and without any interaction between them. Both have also experienced some shortcomings that to some extent has limited their use and results. This paper explores these shortcomings and demonstrates how benchmarking and poor quality cost measurement in some ways is similar and in other ways complement each others’ weaknesses. An integrated framework that combines the two concepts into a powerful approach for assisting an organization’s quality management work is presented. Different points of intersection between the two concepts in this integrated framework are discussed, and it is demonstrated how they support and enhance each other. Such enhancements occur throughout all phases of the benchmarking process, while benchmarking provides an extra dimension to the use of the poor quality cost measurements.  المقدمة